Transmission Model for the Co-infection of HIV/AIDS and Tuberculosis - Pinto, Carla MA; Carvalho, Ana (Journal of Applied Nonlinear Dynamics, 2026)
A mathematical model for the dynamics of co-infection of HIV/AIDS and tuberculosis is developed. The model includes treatment for both HIV and tuberculosis and vertical transmission for HIV/AIDS. The disease-free equilibrium of the model is computed and its local stabil- ity is proved. The reproduction numbers of the full model and of its two submodels, the HIV only model and the TB only model, are also calculated. Numerical simulations show the disease-free equilibrium. Future work will focus on computing the stability of the endemic equilibria.